Temporal change of an Adelie penguin population in the creche-forming period - Masahiro Aoyanagi (Antarctic Record, 1988)
The temporal change of an Adelie penguin population was observed in the B4 colony, Northern Rookery, Cape Bird, Ross Island in the 1978-79 summer season. Between January 1 and 24,1979,after the preparatory observation in late December, the number and position of occupied nests, occupying birds, re-occupying nonbreeders and chicks were observed and recorded on a map at least once a day. Upon abandonment of the nests by the occupant birds, the chicks left their nests to form a creche in the colony. The nest abandonment and the creche formation were completed on January 9 and 10. Simultaneously, the free-nonbreeders entered the colony from the outside of it. Part of the chicks that left their nests gathered closely to form huddles in the creche. The size, shape and position of the huddles varied temporally. The feeding place of chicks changed from their nests to the outside of the nests and then to the outside of the colony with the progress of creche formation.